HUBUNGAN TINGKAT STRES DENGAN KADAR GULA DARAH PADA PASIEN DIABETES MELITUS TIPE II RUMAH SAKIT X - Siti Aminah; Hernandia Distinarista; Tutik Rahayu (Yayasan Healing and Healthcare Education, 2026)
Based on the 2018 National Health Research (RISKESDAS), the prevalence of doctor-diagnosed diabetes mellitus in Banten province reached 2.1%, slightly higher than the national average. Specifically, in Serang City, the capital of Banten Province, the prevalence of diabetes mellitus shows a number that deserves attention. Data from the Serang City Health Office (2023) shows that non-communicable diseases (NCDs) are the most common among the community. As one of the main referral hospitals in Serang City, Sari Asih Serang Hospital also feels the impact of the increasing number of diabetes mellitus sufferers. Based on medical record data from the internal medicine polyclinic, there were 277 patient visits with a diagnosis of diabetes mellitus in the period March to May 2025. Diabetes mellitus sufferers with unstable blood sugar regulation have a two-fold greater risk of experiencing a spike in glucose levels when experiencing stress, compared to diabetes sufferers who have better blood sugar control. Factors that can affect a person's blood sugar levels include lack of exercise, diet, stress, obesity, genetic factors, and consumption of certain medications. The general objective of this study was to determine the relationship between stress levels and blood sugar levels in patients with type II diabetes mellitus. This study is a quantitative study with a cross-sectional design. The population of this study were patients at Sari Asih Hospital in Serang City who suffered from diabetes mellitus. The research sample consisted of 74 participants. The results of the study were carried out with a correlation test with a sig value (2-tailed) of (0.005). So Ho was rejected and Ha was accepted, it can be concluded that there is a relationship between stress levels and blood sugar levels in patients with type 2 diabetes mellitus controlled at the hospital. Sari Asih Serang. And the correlation coefficient value is known to be 0.005a r= 0.005 (r < 0.05).